Pengaruh Pupuk Organik Cair dengan Konsentrasi Urin dan MOL Berbeda terhadap Produksi Rumput Gajah Mini (Pennisetum purpureum cv. Mott) - Fitriana Akhsan; Sukriandi; A. Fajar Kurniawan Amris; Muh. Irmansyah (Universitas Sulawesi Barat, 2020)
Liquid organic fertilizer with the right concentration is expected to be a source of nutrients for the growth of mini elephant grass. The aims of this study were to determine the effect of liquid organic fertilizer with different concentrations of urine and Local Microorganism (LMO) on the production of mini elephant grass. The research method used was a randomized block design (RBD) with 4 treatments and each treatment consisted of 3 groups as replications. The treatments used were liquid organic fertilizer, with concentrations of P0 (as a control), P1 (100 % urine, 0 % LMO), P2 (90 % urine, 10 % LMO) and P3 (85 % urine, 15 % LMO). The results showed that liquid organic fertilizer with different concentrations of urine and MOL had no significant effect on plant height, number of leaves, number of tillers and production of fresh weight (g/clump). The liquid organic fertilizer with different urine and MOL concentrations has no significant effect on the growth and production of mini elephant grass.